Specular microscopy in clinical practice - Sunita Chaurasia; Murugesan Vanathi (Indian Journal of Ophthalmology, 2021)
Specular microscopy is a noninvasive diagnostic tool that allows for in vivo evaluation of corneal endothelium in health and various diseased states. Endothelial imaging helps in the diagnosis and management of several endothelial disorders. The review focuses on the principles of specular microscopy, limitations of endothelial imaging, and its interpretation in common conditions seen in the clinical practice. A thorough PubMed search was done using the keywords specular microscopy, corneal endothelium, and endothelial imaging.